Effects of bubbles in the liquid jet on the air-blast atomization. (15th April 2020) - Wu, Zhao-Wei; Shi, Zhe-Hang; Zhao, Hui; Yao, Feng; Liu, Hai-Feng; Li, Wei-Feng; Xu, Jian-Liang
Abstract: The air-blast atomization with bubbles in the liquid jet was investigated using the high-speed camera and Malvern laser particle size analyzer. The gas was aerated into the liquid jet to form the gas-liquid mixture, which would be atomized by the co-flowing air stream. Results show that droplet size D 32 decreases at the beginning and then increases with the volumetric flow rate of the aerating gas. A formula was derived to delineate the nonmonotonic trend of the droplet size. The relative deviations between the predicted results and experimental results are less than ±5%. A contour map describing the dependence of the droplet size on the aerating gas, liquid jet, and co-flowing air stream was obtained, which could provide some guidance for the further investigations and industrial applications.